Plankton in waters adjacent to the Laje de Santos state marine conservation park, Brazil: spatio-temporal distribution surveys - Bueno, Marilia; Alberto, Samantha Fernandes; Carvalho, Renan de [UNESP]; Costa, Tania Marcia [UNESP]; Ciotti, Aurea Maria; Christofoletti, Ronaldo Adriano (Inst Oceanografico, Univ Sao Paulo, 2017)
The coastal marine plankton plays a major role in ecosystem functioning by linking pelagic and benthonic environments through energy fluxes. Understanding the dynamic of planktonic organisms is also crucial for conservation and management purposes. Plankton was sampled at ten sites in the waters of the PEMLS and the adjacent area, on four different occasions through 2013 and 2015 in order to identify key planktonic groups and protocols for long-term monitoring. Ninety taxa of zooplanktonic organisms were found with holoplanktonic copepods and cladocerans dominating samples. Zooplankton biomass, mortality and taxonomic composition varied both in space and time. Surface chlorophyll-a concentrations varied spatio-temporally. A protocol for monitoring the plankton of the waters in and adjacent to the PEMLS is suggested based on biomass and mortality of zooplankton and biomass of phytoplankton using periodically in situ calibrated ocean color satellite imagery.
Keywords: Marine Protected Area; Plankton Composition; Conservation; Laje de Santos; Monitoring